Effects of Plant-Based Diets on Weight Status in Type 2 Diabetes: A Systematic Review and Meta-Analysis of Randomised Controlled Trials - Grace Austin (MDPI AG, 2021)
Excessive adiposity is a major risk factor for type 2 diabetes (T2D), and dietary patterns are important determinants of weight status. Plant-based dietary patterns (PBDs) are known for their therapeutic effects on T2D. The aim is to systematically review RCTs to investigate the effects of various PBDs compared to regular meat-eating diets (RMDs), in individuals who normally consume a RMD on body weight, BMI, and waist circumference in T2D. RCTs investigating PBDs and body weight, BMI, WC for ≥6 weeks in adults with T2D since 1980 were eligible for inclusion. Seven trials (n = 269) were included in the meta-analysis using random-effects models and expressed as MD (95%Cls). Compared to RMDs, PBDs significantly lowered body weight (−2.35 kg, 95% CI: −3.51, −1.19, p < 0.001), BMI (−0.90 kg/m2, 95% CI: −1.42, −0.38, p = 0.001) and WC (−2.41 cm, 95% CI: −3.72, −1.09, p < 0.001). PBDs alone significantly reduced body weight by 5.1% (−4.95 kg, 95% CI: −7.34, −2.55, p < 0.001), BMI by 5.4% (−1.87 kg/m2, 95% CI: −2.78, −0.95, p < 0.001) and WC by 4.3%(−4.23, 95% CI: −6.38, −2.07, p < 0.001). Interventions not limiting energy intake led to a significant reduction in body weight (−2.54 kg, 95% CI: −4.16, −0.92, p < 0.005) and BMI (−0.91 kg/m2, 95% CI: −1.56, −0.25, p < 0.005). Trials ≥16 weeks had a pronounced reduction in body weight (−2.93 kg, 95% CI: −5.00, −0.87, p = 0.005) and BMI (−1.13 kg/m2, 95% CI: −1.89, −0.38, p < 0.005). These findings provide evidence for the implementation of PBDs for better management of central adiposity in individuals with T2D.